Definisi dan Strategi Manajemen Konflik: Tinjauan Literatur dalam Konteks Pendidikan dan Organisasi - Hanif Achmad Shohiburriyadh; Wilda Ayunin Nufus; Nur Nafi’atul Jannah; Ahmadi Ahmadi; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Conflict is an inseparable part of social interaction within organizational and educational life. When not properly managed, conflict can disrupt institutional stability and effectiveness. Therefore, understanding the definition of conflict and its management strategies is crucial for both academics and practitioners. This study aims to review recent literature on the definition of conflict and conflict management strategies in educational and organizational contexts, guided by two research questions: (1) how is conflict defined in the literature from 2020 to 2025, and (2) what conflict management strategies are most commonly applied across various contexts. The method used is a literature review, with data collected through Google Scholar and the Publish or Perish application using the keyword “definition of conflict.” From a total of 20 identified articles, 18 were selected through a screening process based on recency, open access, and topic relevance. The findings indicate that the definition of conflict is contextual and multidimensional, while the management strategies generally include communication, negotiation, and institutional policy.